POLYMORPHISM OF SMAD7 (RS4939827) AND EIF3H (RS16892766) GENES AS A CRITERIUM OF FIBROSIS PROGRESSION RATE IN PATIENTS WITH CHRONIC HEPATITIS С AND В - Appelhans, O.L.; Usychenko, К.М.; Bazhora, Yu.I.; Usychenko, О.M. (World of Medicine and Biology, 2020)
The purpose of the study was to assess the possibility of the relationship between the gene polymorphism of SMAD family member 7 (SMAD7C> T), the eukaryotic translation initiation factor (eIF3hC> A) and the degree of liver fibrosis in a pilot project in patients with chronic hepatitis B and chronic hepatitis C. Differences in the frequencies of alleles of the SMAD7 gene in the ethnically homogeneous group of residents of the Odessa region in patients with chronic hepatitis C and chronic hepatitis B compared to healthy individuals (p
Keywords: SMAD family member 7; eukaryotic translation initiation factor eIF3h; chronic hepatitis C; chronic hepatitis B